Corporate Culture and Green Human Resource Management in Selected Oil and Gas Industries in Rivers State - Letam, Don-Baridam (Journal of Advanced Research in Petroleum Technology & Management; Vol 4 No 3&4 (2018): Journal of Advanced Research in Petroleum Technology & Management, 2021)
This study examined the relationship between corporate culture and green human resource management practices. Using data from 386 employees, randomly drawn from five selected multinational oil and gas industries in Rivers State, the Pearson product moment correlation was used to measure the relationship between the components or proxies of the independent variable and the measures of the dependent variables. The SPSS version 20 was employed for the analysis. Results indicate that there is a positive and significant relationship between corporate culture and green human resource management practices. The study also revealed that corporate culture drives the green human resource practices of the organization. Based on this, it was therefore recommended that organizations need to sustain positive and supportive work cultures that enables the effective adoption of green human resource management practices.